Porous honeycomb structures formed from interconnected MnO(2) sheets on CNT-coated substrates for flexible all-solid-state supercapacitors - Ko, Wen-Yin (Sci Rep, 2016)
The use of lightweight and easily-fabricated MnO(2)/carbon nanotube (CNT)-based flexible networks as binder-free electrodes and a polyvinyl alcohol/H(2)SO(4) electrolyte for the formation of stretchable solid-state supercapacitors was examined. The active electrodes were fabricated from 3D honeycomb porous MnO(2) assembled from cross-walled and interconnected sheet-architectural MnO(2) on CNT-based plastic substrates (denoted as honeycomb MnO(2)/CNT textiles).These substrates were fabricated through a simple two-step procedure involving the coating of multi-walled carbon nanotubes (MWCNTs) onto commercial textiles by a dipping-drying process and subsequent electrodeposition of the interconnected MnO(2) sheets onto the MWCNT-coated textile. With such unique MnO(2) architectures integrated onto CNT flexible films, good performance was achieved with a specific capacitance of 324 F/g at 0.5 A/g. A maximum energy density of 7.2 Wh/kg and a power density as high as 3.3 kW/kg were exhibited by the honeycomb MnO(2)/CNT network device, which is comparable to the performance of other carbon-based and metal oxide/carbon-based solid-state supercapacitor devices. Specifically, the long-term cycling stability of this material is excellent, with almost no loss of its initial capacitance and good Coulombic efficiency of 82% after 5000 cycles. These impressive results identify these materials as a promising candidate for use in environmentally friendly, low-cost, and high-performance flexible energy-storage devices.